Characterization of Calcium Oxide Treated Lead–Lead Dioxide Vitroceramics from Recycled Automobile Batteries by X-Ray Diffraction, Infrared and Ultraviolet–Visible Spectroscopy, and Voltammetry. (13th October 2022) - Piscoiu, D. N.; Rada, S.; Macavei, S.; Vermesan, H.; Culea, E.
Abstract: Today the number of automobiles is increasing, and hence, the demand for lead-acid batteries is enhanced. Improvements regarding reusable car batteries implies the elimination of disadvantages of the traditional recycling methods. The purpose of this work is: (i) to recycle the spent plates from a car battery with high wear by an eco-innovative method and (ii) to characterize the prepared materials and to characterize their electrochemical performance for new electrodes for batteries. The prepared samples were investigated by X-ray diffraction, infrared and ultraviolet–visible spectroscopy, and cyclic voltammetry and linear sweep voltammetry. The results show that following the addition of calcium ions into the lead–lead dioxide recycled matrix and the formation of Ca3 (SO3 )2 SO4 crystalline phase were evident. These results suggest that no emissions of sulfur oxides into the atmosphere.